Short Term Effect of Corona Virus Diseases Vaccine on the Menstrual Cycles - M M Al-Mehaisen L; A Mahfouz I; Khamaiseh K; N AL-Beitawe S; Al-Kuran OAH (Dove Medical Press, 2022)
Lama M M Al-Mehaisen,1 Ismaiel A Mahfouz,1 Khaldoun Khamaiseh,1 Soha N AL-Beitawe,2 Oqba AH Al-Kuran3 1Faculty of Medicine, Al Balqa Applied University, Al Salt, Jordan; 2Faculty of Medicine, Al-Yarmouk University, Irbid, Jordan; 3Faculty of Medicine, Jordan University Hospital, Amman, JordanCorrespondence: Lama M M Al-Mehaisen, Department of Obstetrics and Gynaecology, Faculty of Medicine - Al Balqa Applied University, B O Box 206, Al Salt, Jordan, Tel +96253491111, Email lmehaisen@bau.edu.joBackground: The latest threat to world health is coronavirus disease-2019 (COVID-19), and the exact death rate of SARS-CoV-2 infection is still to be explored and varies widely throughout the world. Inactivated virus vaccines, recombinant viral vaccines, subunit vaccines, DNA vaccines, and attenuated vaccinations have all been investigated in the hunt for an optimal SARS-CoV vaccine. Some women had menstrual abnormalities after immunisation, including heavy menstrual bleeding (menorrhagia), frequent bleeding (metrorrhagia/polymenorrhea), and postmenopausal haemorrhage. Vaccine-induced thrombocytopenia might be one of the underlying reasons.Purpose: The aim to carry out this study was to survey by recruiting the female participants who were vaccinated with one or two shots of the available vaccine and observe short-term menstrual changes.Patients and Methods: This web-based survey cross-sectional study included women who were above 18 years, had the vaccine at least one month (one menstrual period) before participating in the study, had access to social media platforms and were willing to take part in the study. Women were excluded if, at the time of the study, they were pregnant or had amenorrhea of more than 6 months.Results: Analysing the menstrual flow more, we saw that 24.5% of the patients had increased flow, while 15.5% had reduced flow which for both changes in the flow, the p-value was 0.017. However, 23.65 showed delayed periods, and 51.6% showed no changes. The changes in the timing were significant, indicating a p-value of 0.008. The study will be a significant contribution to the literature as this pandemic is new, and the vaccination against COVID-19 is still in the trial phase.Conclusion: We observed in our study that there was a change in the menstruation timings and flow after vaccination. However, further longitudinal studies are needed to conclude the impact of the COVID-19 vaccine on the menstruation cycle.Keywords: COVID-19, menstrual abnormalities, menstrual changes, menstrual flow, short-term effect, vaccination